RitaHem9Tayler
RitaHem9Tayler
16-06-2016
Mathematics
contestada
Simplify the expression: (3xy)-1
Respuesta :
unidonuthorse
unidonuthorse
19-06-2016
-1(3xy) = -1 * 3xy = -3xy
Answer Link
VER TODAS LAS RESPUESTAS ( 96+ )
ACCESS MORE
Otras preguntas
Svalks If x = 6, find the value of a) x + 4 b) 3x c) Ă
what country started the tradition of exchanging gifts at christmas
Please help me! ty ty :)
If the sentence below contains an error in capitalization, choose the sentence with the correct capitalization. If there are no errors, chose the No Error optio
Write an essay about how the revolutionary war wasn't revolutionary. use minimum 5 paragraphs and use and cite evidence
Hello Brainly Community, please help me.. Can anyone solve this equation by factoring? x²-x-20=0 Math homework.. please help. No spam..
Write a cause and effect sentence
Solve x2 + 4x = 4 for x by completing the square. x = −4 x = 0 x equals plus or minus 2 times the square root of 2 plus 2 x equals plus or minus 2 times the squ
WHAT IS 12+23+67+10+19+60=
Which of the following values would complete the ordered pair if the point is on the graph of f(x) = -2x +3? (-1,_) (fill in the blank) 510-4